2007
DOI: 10.3354/meps07144
|View full text |Cite
|
Sign up to set email alerts
|

Differences between biota in anthropogenically fragmented habitats and in naturally patchy habitats

Abstract: The extent to which the 'fragmented' properties of a landscape have actually been caused by anthropogenic fragmentation is often unknown. We can, however, understand links between spatial patterns of habitat in the current landscape and the biota. Built seawalls in Sydney Harbour, Australia, appear to fragment the natural, intertidal habitat. Rocky shores naturally occur, however, in a landscape of 'fragments', i.e. as patches of natural habitat separated by other natural habitats. To examine the extent to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Seawalls and similar infrastructure are built to prevent erosion and for commercial, residential, or recreational purposes. They replace natural intertidal or subtidal rocky and sedimentary shores, potentially disrupting connectivity among populations (Bulleri & Airoldi 2005), providing stepping stones or corridors for spread of invasive species (Bulleri et al 2006), and affecting assemblages in adjacent habitats (Goodsell et al 2007). Environmental impacts of 'armouring' of shores are likely to worsen with climatic change, due to rising sea levels and increased frequency of storms, requiring more artificial protection of coastlines.…”
Section: Introductionmentioning
confidence: 99%
“…Seawalls and similar infrastructure are built to prevent erosion and for commercial, residential, or recreational purposes. They replace natural intertidal or subtidal rocky and sedimentary shores, potentially disrupting connectivity among populations (Bulleri & Airoldi 2005), providing stepping stones or corridors for spread of invasive species (Bulleri et al 2006), and affecting assemblages in adjacent habitats (Goodsell et al 2007). Environmental impacts of 'armouring' of shores are likely to worsen with climatic change, due to rising sea levels and increased frequency of storms, requiring more artificial protection of coastlines.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the predictions, however, natural patches had less variability at the scale of kilometres (among shores) than did complete or mixed fragments. In contrast, the numbers of taxa on rocky shores in Sydney Harbour were more variable in natural patches than in complete or mixed fragments (Goodsell et al 2007). Interestingly, variability on a scale of metres (among sites) was smaller in complete fragments than in natural patches, at least at mid-shore levels.…”
Section: Discussionmentioning
confidence: 97%
“…There is convincing evidence, however, that seawalls contain different and fewer taxa (Chapman 2003, Bulleri et al 2005, and there are differences in the size, fecundity (Moreira et al 2006) and behaviour ) of organisms on seawalls compared to those on rocky shores. Moreover, complete fragments in Sydney Harbour are smaller and further away from each other than are natural patches (Goodsell et al 2007). Changes to the configuration and composition of coastal landscapes caused by replacing natural with artificial habitat may have predictable ecological consequences for biota on rocky shores that have been fragmented.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The above mentioned studies have generally compared the assemblage structure on artificial and natural shores while little is known on how these structures affect the structure of adjacent rocky intertidal communities (but see Goodsell et al, 2007). Work done on other systems including mangrove forests (Kelaher et al, 1998), fish assemblages (Clynick et al, 2008) and soft-sediment habitats (see Bertasi et al, 2007 and references therein) has shown that the influence of artificial structures can extend well beyond the very communities they support.…”
Section: Introductionmentioning
confidence: 99%